2020
DOI: 10.1002/adom.201901658
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Region Resonant Meander Metamaterial

Abstract: Metamaterials are engineered structures designed to interact with electromagnetic radiation, whereby the frequency range in which metamaterials respond depends on their dimensions. In this paper, it is demonstrated that a metamaterial can be functional in more than one frequency region. An advanced metamaterial is demonstrated that can interact with both terahertz (THz) and near‐infrared (NIR) frequencies, concurrently. This work exploits meander line resonators with nanoscale linewidth distributed over micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…[27][28][29][30] On the other hand, the spectral tunability is an important factor affecting the performance of the MM. A single dual-region MM based on meander line resonators has been reported by Manjunath et al 31 The MM produced in this work can be functional in both THz and NIR frequencies simultaneously. Although the THz resonant frequency can be adjusted by increasing the gap between meta-atoms while having a negligible impact on the NIR transmission spectrum, the NIR resonant frequency cannot be tuned independently without affecting the THz response.…”
Section: Introductionmentioning
confidence: 68%
“…[27][28][29][30] On the other hand, the spectral tunability is an important factor affecting the performance of the MM. A single dual-region MM based on meander line resonators has been reported by Manjunath et al 31 The MM produced in this work can be functional in both THz and NIR frequencies simultaneously. Although the THz resonant frequency can be adjusted by increasing the gap between meta-atoms while having a negligible impact on the NIR transmission spectrum, the NIR resonant frequency cannot be tuned independently without affecting the THz response.…”
Section: Introductionmentioning
confidence: 68%
“…Conventional metamaterials can achieve the resonant response and can be operated at a combination of dual and triple‐band. [ 12 , 27 , 28 , 29 , 30 , 31 ] They are designed for a specific application, due to the difficulty and low flexibility of adapting their functions once fabricated. Therefore, it is challenging to fabricate metamaterials with a single type of meta‐atom with ultra‐broadband adaptability in controlling EM waves, due to the huge diversity between the critical subwavelength feature sizes of the artificial atom.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 8 , 9 ] However, the critical feature sizes of meta‐atom spans serval orders of magnitude in length scale, from few nanometers to tens of centimeters, almost all the metamaterials are designed to operate at a specific frequency, [ 10 ] a narrow band, [ 11 ] or a combination of dual and triple‐band. [ 12 , 13 ] Nevertheless, once the metamaterials are fabricated, their functions will be fixed or have only a limited adjustable range. Therefore, it is challenging to fabricate metamaterials with a single type of meta‐atom with ultra‐broadband adaptability in controlling EM waves.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-spectral metasurfaces have been widely used in other fields, such as absorbers, resonators, and filters [32]. For example, Man-junath et al, presented a single dual-region metasurface based on meander line resonators, which can interact with near-infrared and THz waves at the same time [33]. Grant et al, reported a synthetic multi-spectral metasurface achieved through hybridizing optical plasmonic filtering with mid-IR and THz absorption, thereby manipulating radiation in multiple regions simultaneously [34].…”
Section: Introductionmentioning
confidence: 99%